Climate risks and financial stability - Battiston, Stefano; Dafermos, Yannis; Monasterolo, Irene (Journal of financial stability, 2021)
Climate change has been recently recognised as a new source of risk for the financial system. Over the last years, several central banks and financial supervisors have recommended investors and financial institutions to assess their exposure to climate-related financial risks. Central banks and financial supervisors have also started to design scenarios for climate stress tests - to- assess how vulnerable the financial system is to climate change. Nevertheless, the financial community falls short of methodologies that allow the successful analysis of the risks that climate change poses to financial stability. Indeed, the characteristics of climate risks (i.e., deep uncertainty, non-linearity and endogeneity) challenge traditional approaches to macroeconomic and financial risk analysis. Embedding climate change in macroeconomic and financial analysis using innovative perspectives is fundamental for a comprehensive understanding of the macrofinancial relevance of climate change. This Special Issue is devoted to the relation between climate risks and financial stability and represents the first comprehensive attempt to fill methodological gaps in this area and to shed light on the financial implications of climate change. It includes original contributions that use a range of methodologies – such as network modelling, dynamic evolutionary macroeconomic modelling and financial econometrics – to analyse climate-related financial risks and the implications of financial policies and instruments aiming at the low-carbon transition. The research insights of these contributions can inform the decisions of central banks and financial supervisors about the integration of climate change considerations into their policies and financial risk assessment.